2013
DOI: 10.1134/s1063772913070056
|View full text |Cite
|
Sign up to set email alerts
|

Infrared emission and the destruction of dust in HII regions

Abstract: The generation of infrared (IR) radiation and the observed IR intensity distribution at wavelengths of 8, 24, and 100 µm in the ionized hydrogen region around a young, massive star is investigated. The evolution of the HII region is treated

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 23 publications
6
85
0
Order By: Relevance
“…It has been demonstrated that a non-negligible fraction of the 70 μm emission comes from stochastically heated very small grains (e.g., Compiègne et al 2010;Pavlyuchenkov et al 2013); this is especially true when an H ii region is present along the line of sight.…”
Section: Physical Conditions Of the Cold Ismmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that a non-negligible fraction of the 70 μm emission comes from stochastically heated very small grains (e.g., Compiègne et al 2010;Pavlyuchenkov et al 2013); this is especially true when an H ii region is present along the line of sight.…”
Section: Physical Conditions Of the Cold Ismmentioning
confidence: 99%
“…The 24 μm emission is bright in the direction of the center of the H ii region, a region devoid of PAHs emission. As shown by the radiative transfer model of Pavlyuchenkov et al (2013) this emission comes from very small dust grains (VSGs; a few nm in size) located inside the ionized region, and out of thermal equilibrium after absorption of ionizing photons. Diffuse 24 μm emission is also observed in the direction of the neutral PDR surrounding the ionized region.…”
Section: Distance Morphology and Nature Of The Ionized Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Pavlyuchenkov et al (2013), we consider that the dust filling the H II region and penetrating into the bow shock is similar of that of the ISM. Our radiative transfer calculations nevertheless suffer from uncertainties regarding to the composition of this ISM dust.…”
Section: Surrounding H II Region and Dust Compositionmentioning
confidence: 99%
“…IR observations of thermal dust emission is an attractive possibility because winds from hot stars are dust-free, whereas H  regions contain a normal ISM dust distribution, with the exception of PAHs that are destroyed by ionizing radiation (Povich et al 2007;Pavlyuchenkov et al 2013). O stars are luminous radiation sources, and so even though only a small fraction of the stellar radiation is absorbed by dust, the re-emitted radiation is often more luminous than that of all gas-cooling radiation (Meyer et al 2014).…”
Section: Introductionmentioning
confidence: 99%